Author’s Modality of Didactic Text and Reader’s Perception (by Example of A. G. Dymov’s “Adab”) - I. A. Kazharova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
Aspects of the author’s modality manifestation and related features of didactic text perception are considered. The authors briefly describe the reflection of didactic discourse in the literary reception, argue the importance of identifying the author’s modality in the moralizing texts presented in the educational literature. Based on a specific material, the authors study the forms of expression of the author’s consciousness and the specifics of perception of the didactic text. The defining role of background knowledge in a situation when the reader and the author of a didactic work belong to different eras is shown. Expressions of modality in the present article are determined by the choice of genre and interaction between the author’s consciousness with the laws of the genre, points of view dominant in the text and the regularities of their interactions, the choice of character and characters, the degree of categoricity of the author’s “I.” Examples are given from the didactic works of A. G. Dymov (“Adab”), whose work has not yet been considered from the position of semantic expressiveness of the subject of the author’s plan involved in it. Despite the fact that the measure of subjectivity in a didactic text intended for educational purposes should be minimal, and their aesthetics can be unassuming, it is proved on a specific material that the recognition of forms of author’s modality allows not only to specify the author’s value attitudes, but also to judge in many ways the reasons that hold attention when reading such texts.